Similar effects of milk protein and blends of milk and plant‐based protein on appetite‐related hormones in 7‐ to 8‐year‐old healthy Danish children: secondary analyses from the PROGRO randomised trial. (10th March 2022) - Larnkjær, Anni; Grenov, Benedikte; Ritz, Christian; Michaelsen, Kim F.; Mølgaard, Christian
Abstract: Aim: The effect of different protein sources on the appetite‐related hormones in children is largely unknown. We investigated the effect of milk protein versus blends of milk and rapeseed protein on plasma leptin and adiponectin in children. Methods: We included 88 Danish 7‐ to 8‐year‐old children randomised to receive 35 g protein/day for 4 weeks in 2018 as either milk protein or blends of milk and rapeseed protein (ratio 54:46 or 30:70). Outcomes included absolute and fat mass‐adjusted adiponectin and leptin measured at baseline, Weeks 1 and 4. Results: There was no difference in changes in absolute and fat mass‐adjusted adiponectin and leptin after 1 or 4 weeks between the three groups ( p ≥ 0.100). Leptin increased within all groups ( p ≤ 0.046). Combining the three groups, leptin and fat mass‐adjusted leptin increased by 23% (95% CI 11;35) and 17% (6.4;29) during the intervention respectively (both p ≤ 0.001). Adiponectin variables did not change during the intervention period. Conclusion: There were no differences between milk protein and blends of milk and rapeseed protein on absolute and fat mass‐adjusted leptin and adiponectin in healthy children with a habitual intake of milk. However, leptin increased within all three groups. Future studies should further investigate effect on appetite‐related hormones of rapeseed protein alone.